Determinants of Rural Poverty in Western Indonesia 2019-2023 - I Wayan Suparta; Lola Oktaviani (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the effect of Farmer Exchange Rate (NTP), agricultural labor, and education on the rural poverty rate in western Indonesia during the 2019-2023 period. Using panel data from 17 provinces and the Fixed Effect Model (FEM) method, the results show that the three independent variables have a negative and significant effect on rural poverty. These findings identify that improving farmers' welfare, optimizing labor in the agricultural sector, and improving education can be effective strategies in reducing poverty in rural areas.